Online learning barriers encountered by university lecturers in using communication strategies: a phenomenological approach - Lumadi, Mutendwahothe Walter; Mabidi, Ndamulelo Innocentia (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
The intent of the research is to conduct a phenomenological study about the lived experiences of South African university lecturers. The experiences of the lecturers are explored with regard to the online learning barriers encountered when using communication strategies. The Community of Inquiry and Heidegger’s interpretive phenomenological framework were employed to comprehend the lecturers’ experiences of designing and implementing teaching using online technologies, such as smartphones, emails, SMSs, WhatsApp, Facebook, tutorial letters and discussion forums of the learning management system when communicating with students. In view of the current situation with all the intricacies, deficiencies, and challenges of online teaching and learning, the findings showed that the lecturers’ teaching presence is not clearly discernable. Nevertheless, there seem to be attempts by lecturers to ensure that their teaching and social presence are better integrated, albeit in an amorphous manner.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (3) (2022) Special Issue
Keywords: Phenomenology; Online Communication; Lived Experience; Strategies; Google; Phenomenology; Web-based instruction; Social media in education